ChemInform Abstract: Remarkable Effect of CF3CH2OH for the Halogen Induced Oxidative Rearrangement Reaction of Aminals Leading to 3, 4‐Dihydroquinazolines. Issue 31 (11th July 2013) - Murai, Kenichi; Shimura, Masato; Nagao, Ryu; Endo, Daisuke; Fujioka, Hiromichi
Abstract A general method for promoting oxidative rearrangement reactions of aminals generating 3, 4‐dihydroquinazolines is developed.